Tax Planning Practices and Book-Tax Differences in Multinational Companies: Evidence from Saudi Arabia - Alomair, Mohammed (Journal of Cultural Analysis and Social Change, 2025)
This research investigates how tax planning strategies influence the magnitude of book-tax differences within multinational corporations operating in Saudi Arabia. The empirical analysis examines 25 actively traded multinational firms listed on the Saudi Stock Exchange between 2017 and 2020, yielding 100 firm-year observations. The study deliberately excludes financial services entities due to their distinct operational characteristics and regulatory frameworks that differ substantially from industries where conventional tax planning mechanisms are typically implemented. Using multiple regression analysis, the study employs effective tax rates as proxies for tax planning intensity, distinguishing between cash effective tax rate (CASH ETR) and GAAP effective tax rate (GAAP ETR). The regression model demonstrates exceptional explanatory power (R² = 0.988, F = 1164.336, p < 0.001), indicating that tax planning variables explain 98.8% of the variation in book-tax differences. The findings reveal statistically significant relationships: CASH ETR exhibits a positive association with book-tax differences (β = 0.092, t = 2.031, p = 0.045), while GAAP ETR demonstrates a strong negative relationship (β = -9.510, t = 88.228, p < 0.001). Control variables including firm size, leverage, sales growth, liquidity, and profitability show no significant effects (all p > 0.10), suggesting that tax planning strategies dominate other factors in explaining book-tax divergence. The results confirm that multinational enterprises strategically exploit jurisdictional differences in tax regulations, employ transfer pricing arrangements, and leverage bilateral tax treaties to optimize their global tax positions, consequently generating substantial book-tax differences. These findings provide first-time empirical evidence from an emerging Middle Eastern economy and offer actionable insights for investors assessing earnings quality, regulators designing enforcement strategies, and policymakers evaluating tax system effectiveness.